2006
DOI: 10.1681/asn.2006080909
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid, the Metabolic Syndrome, and Renal Disease

Abstract: Metabolic syndrome, characterized by truncal obesity, hypertriglyceridemia, elevated BP, and insulin resistance, is recognized increasingly as a major risk factor for kidney disease and also is a common feature of patients who are on dialysis. One feature that is common to patients with metabolic syndrome is an elevated uric acid. Although often considered to be secondary to hyperinsulinemia, recent evidence supports a primary role for uric acid in mediating this syndrome. Specifically, fructose, which rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
131
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(136 citation statements)
references
References 39 publications
4
131
0
1
Order By: Relevance
“…10 -12 Uric acid may cause these conditions through inhibition of endothelial nitric oxide bioavailability, activation of the renin-angiotensin system, and/or direct effects on endothelial cells and vascular smooth muscle cells. 3 Clinical support for this hypothesis is provided by data from the Health Professionals' Follow-up Study, which suggested that elevated serum uric acid is a risk factor for development of hypertension in younger men. 13 Both direct kidney injury and preexisting systemic hypertension may lead to incident kidney disease associated with uric acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 -12 Uric acid may cause these conditions through inhibition of endothelial nitric oxide bioavailability, activation of the renin-angiotensin system, and/or direct effects on endothelial cells and vascular smooth muscle cells. 3 Clinical support for this hypothesis is provided by data from the Health Professionals' Follow-up Study, which suggested that elevated serum uric acid is a risk factor for development of hypertension in younger men. 13 Both direct kidney injury and preexisting systemic hypertension may lead to incident kidney disease associated with uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…1 Elevated levels of serum uric acid are associated with the development of hypertension and are common in individuals with diabetes and diabetes risk factors. 2,3 Accordingly, uric acid, via effects on renal vasoconstriction and systemic hypertension, may mediate aspects of the relationship between hypertension and kidney disease.…”
mentioning
confidence: 99%
“…4 Uric acid (UA) is the end product of purine metabolism in humans, and approximately 70% of UA are eliminated by the kidney. 5 Several prospective studies have documented that the elevated serum uric acid (SUA) level is associated with the development of T2DM itself, 6 hypertension, 7 cardiovascular disease 8 and the risk factors of metabolic syndrome (MS).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hyperuricemia leads to the deposition in tissues of monosodium urate (MSU) crystals, which are proinflammatory and cause gout, a form of arthritis affecting 3-5 million people in the United States (9)(10)(11). Both hyperuricemia itself and gout are strongly associated with conditions thought to result from or to cause oxidative stress, including obesity, hypertension, the metabolic syndrome, and cardiovascular disease (CVD) (12)(13)(14)(15)(16)(17)(18).The role of urate in these conditions remains uncertain.…”
mentioning
confidence: 99%